Valerian and Hops Combination Versus Escitalopram in Models of Depression and Anxiety: A Cross-talk with Oxidative Stress - Gammoh, Omar; Aburubaiha, Zaid; Mayyas, Amal; Alkatib, Walid; Masarweh, Renad; Elhajji, Feras; Alqudah, Abdelrahim (Jordan Journal of Pharmaceutical Sciences, 2023)
Depression and anxiety disorders are the most common mental health problems and are associated with oxidative stress. Although famous for its anxiolytic effect, the antidepressant effect of the valerian-hops combination was not previously studied, also the relationship between the sedative effect of valerian-hops and oxidative stress markers is unclear. The current research has two objectives: (1) to compare the antidepressant effect of valerian-hops with escitalopram and (2) to evaluate the sedative/anxiolytic effects of valerian-hops in relation to oxidative stress markers namely Nitric Oxide (NOx), inducible Nitric Oxide Synthase (iNOS) and Super Oxide Dismutase (SOD). Two models were employed using BALB/c mice: A normal condition depression model in which mice were divided into: control, valerian-hops-treated (100mg/kg), and escitalopram-treated (10mg/kg) groups one hour before the open field test, the elevated plus-maze test, and the forced swim test and an anxiety model in which mice were divided into: unstressed naïve, control (stressed), valerian/hops (100mg/kg), and escitalopram (10 mg/kg) groups treated for three weeks; acutely restrained for 6 hours and sacrificed, serum was obtained to detect NOx, iNOS and SOD activity. In the depression model, valerian-hops demonstrated antidepressant activity similar to escitalopram (p>0.05). In the anxiety model, the valerian-hops treated mice demonstrated a profound sedative effect in all behavior paradigms (p<0.05), and normalized the anxiety-induced NOx levels and SOD activity (p<0.05). Under normal conditions, the valerian-hops combination exerts an antidepressant effect similar to escitalopram while in stress/anxiety conditions it exerts profound sedative and antioxidant effects.